Single atomically anchored iron on graphene quantum dots for a highly efficient oxygen evolution reaction. (June 2021) - Chang, C.-Y.; Kashale, A.A.; Lee, C.-M.; Chu, S.-L.; Lin, Y.-F.; Chen, I-W.P.
Abstract: Single-atom catalysts (SACs) supported on carbon-based materials are very promising for maximizing their electrocatalytic activity. However, carbon-based SACs are primarily bonded with carbons, resulting in an inferior performance in the oxygen evolution reaction (OER). Herein, we develop a novel coordination adsorption strategy for the synthesis of a monodispersed Fe(NO)2 moiety anchored on the nitrogen sites of the nitrogen-doped graphene quantum dots (N-GQDs) to form a Fe(NO)2 –N-GQDs complex as an efficient OER catalyst. The resultant Fe(NO)2 –N-GQDs complex exhibits a highly stable overpotential of 270 mV at a current density of 10 mA cm −2 and a Tafel slope of 48 mV dec −1 together with long-term durability, which greatly outperforms the state-of-the-art RuO2 . Our finding emphasizes the role of electron-transfer resistance changes during a simple synthesis method to enhance electrocatalytic efficiency. Therefore, this work will envision numerous opportunities for creating novel-type carbon-based SACs via nitrogen–metal coordination as highly robust OER catalysts. Graphical abstract: Image 1 Highlights: Graphene quantum dots are synthesized for electrolysis application. Atomically anchored iron is doped on graphene quantum dots. Oxygen evolution reaction performance of the iron-doped-graphene quantum dots is evaluated. Atomically dispersed iron catalyst on graphene quantum dots significantly reduces overpotential for the oxygen evolution reaction.